LEMaC-DE01/16: Methodology for determining effective structural contribution in unpaved roads using Light Weight Deflectometer (LWD) without geophones and back-calculation according to AASHTO93 Guide - Rivera, José Julián (My University, 2021)
The use of LWD in flexible pavement structural designs is increasing. The LWDs are offered under 2 typologies; with or without geophones to set the deflection bowl. LWDs with geophones allow to apply mechanistic analysis directly, but LWDs without geophones not. For this reason, the LEMaC Center for Road Research UTN FRLP - CIC PBA (Argentina) analyzes this problem through a research project; their results allow the use of LWD without geophones in pavement design using the AASHTO93 Guide. This ``short report'', as allowed by the Letters Academy, presents a summary of the tasks performed and the work procedure developed. No section of conclusions and exhaustive antecedents and studies of the models presented are included, due to the limit imposed on the number of words for these ``short reports''. This information can be consulted in the ``Correlation model for the use of modulus back-calculation on LWD measurements'' (Rivera & Alderete, 2012).
Keywords: Low-traffic roads; Light weight deflectometer; AASHTO93 Guide; Back-calculation; Pavements